2013
DOI: 10.1016/j.rmed.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of three clinical phenotypes of chronic obstructive pulmonary disease (COPD)

Abstract: In COPD, emphysematous patients present worse pulmonary function and greater dyspnea, although there were no differences in the use of hospital health care resources. The greater comorbidity in Group 2 patients may require specific strategies in this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
3
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 39 publications
(18 reference statements)
11
82
3
6
Order By: Relevance
“…If this was accurate, and assuming that all ACO diagnoses were confirmed by medical record review (100%), under this scenario the estimated ACO prevalence would be 11%, which is consistent with a prior observational study. [11] Our findings of a greater comorbidity burden, medication use, and costs in the claims-positive ACO cohort compared with the claims-positive asthma and COPD cohorts were consistent with prior studies. [18] However, the lower costs observed in the confirmed ACO cohort differed from prior studies that showed ACO patients with higher resource utilization and costs.…”
Section: Comparisons With Prior Studiessupporting
confidence: 89%
See 2 more Smart Citations
“…If this was accurate, and assuming that all ACO diagnoses were confirmed by medical record review (100%), under this scenario the estimated ACO prevalence would be 11%, which is consistent with a prior observational study. [11] Our findings of a greater comorbidity burden, medication use, and costs in the claims-positive ACO cohort compared with the claims-positive asthma and COPD cohorts were consistent with prior studies. [18] However, the lower costs observed in the confirmed ACO cohort differed from prior studies that showed ACO patients with higher resource utilization and costs.…”
Section: Comparisons With Prior Studiessupporting
confidence: 89%
“…[9,11] These discrepancies between our study and prior studies might be attributed, in part, to the quantity and quality of available medical records.…”
Section: Comparisons With Prior Studiescontrasting
confidence: 85%
See 1 more Smart Citation
“…A small pro- 17,41,48 . An important phenotype is COPD overlapping bronchial asthma that is characterised by the presence of either 2 major criteria, or 1 major and at least 2 minor criteria showing a persistent combination of clinical presentation that is typical for both conditions 3,8,42,[49][50][51] . Table 1 gives an overview of those 6 basic COPD phenotypes, which occasionally might occur simultaneously in clinical practice (e.g.…”
Section: Clinical Disease Course and Phenotypesmentioning
confidence: 99%
“…En los servicios de neumología el 43,2% presentó fenotipo enfisematoso, el 44,7% bronquitis crónica y el 12,1% FMEA (23). En nuestra opinión estos estudios, con una muestra pequeña y de pacientes más graves seguidos o ingresados en el medio hospitalario, sobreestiman la verdadera prevalencia de los diferentes fenotipos clínicos.…”
Section: Discussionunclassified